Eco da comunicação e da inovação na universidade: intersecções entre o ecossistema midiático e o ecossistema inovativo - Fernandes, Fabio Frá (2023)
How are the media, communication, and organizational environments of the innovation ecosystem in universities configured? This was the problem-question that guided this study, with its objectification centered on the innovative ecosystem of federal universities headquartered in the state of Rio Grande do Sul, Brazil, namely: the Federal University of Rio Grande do Sul (UFRGS), the Federal University of Santa Maria (UFSM), the Federal University of Pelotas (UFPel), the Federal University of Health Sciences of Porto Alegre (UFCSPA), and the Federal University of Pampa (Unipampa). In action, its general objective sought to unveil the echo of communication and innovation in the universities of Rio Grande do Sul in the light of Media Ecology and the philosophy of Marshall McLuhan, while reviewing theoretical and research approaches in the field of Media Ecology and the innovative phenomenon, identifying the innovative organizational macro-system, recognizing the organizational mesocomplex for the generation and promotion of innovative products and services, verifying the organizational micro-processes for circulation, visibility, and ecosystemic legitimacy, and understanding the intersections between the media ecosystem and the innovation system in the objectified universities. Given the problematization of the empirical object in conjunction with the specific objectives, the research sought in Media Ecology and Marshall McLuhan's philosophy, especially in his figure-ground reversal method, laid the foundations to support both theoretical-epistemological and theoretical-methodological approaches. Given the theoretical-practical, contemporary, and complex nature of the problem at hand, an inductive method was adopted, complemented by the triangulation of approaches common to exploratory, descriptive, and explanatory research. Due to the flexibility in choosing techniques and procedures in the appropriation of these approaches, three techniques for data and information collection were developed, each formatted from distinct but inseparable analyticalinvestigative lenses. Through bibliographic probing, the literature was reviewed. Documentary and conversational probes allowed for a realistic understanding of innovative systems in federal universities in Rio Grande do Sul. This not only filled gaps in the object of study but also allowed the research to delve into the complexities of the ecosystemic phenomenon of innovation. Configuration probes, on the other hand, were necessary to create more detailed representations of the organizational structures of innovation ecosystems while expanding the perception of the media environments that make up the current media ecosystem. Through the figure-ground reversal method, the particularities that each element possesses emerged, moving them from the background to the central focus of visualization. This process allowed for a more precise and concrete representation of both the innovation ecosystem and the communication and media ecosystem. From that point on, the innovation ecosystem of universities with main campuses in the state of Rio Grande do Sul was configured, organized into three systemic-processual levels: the innovative organizational macro-system, which encompasses the structures and representations of an innovation ecosystem in higher education institutions; the organizational mesocomplex for the generation and promotion of innovative products and services, where we classified the arrangements and layers of the innovative phenomenon within these institutions; and organizational micro-processes for circulation, visibility, and ecosystemic legitimacy, which encompass the stages involving the diffusion of the innovative phenomenon. Additionally, the same process was applied to the communication and media fields to develop a unique configuration for the media ecosystem, which, in turn, was composed of twelve media environments, each bringing together various systems to perform specific functions or allow users to assign desired functions to them, which can be integrated into different devices. These environments are interconnected by transmedia networks or environments composed of hardware devices and software systems. In response to the problem and, by extension, the objectives, the echo of communication and innovation in the university is configured through the intersections between the media ecosystem and the innovation ecosystem. The interaction between these ecosystems is clear, as different media environments play various strategic roles in the ecology of innovation. On the one hand, be skillfully adopted to position organizational communication, attentive to the phenomenon of mediatization, as a strategic field of practices and processes for innovation and creativity environments. On the other hand, not only communication but also media environments act as means to operationalize innovative products, processes, and services, all grounded in technologies interconnected through transmedia networks.